Successful pregnancies after neonatal aortic thrombosis, childhood arterial repair, and a deficient pelvic vasculature. Issue 6 (14th April 2018) - Troëng, Thomas; Bergqvist, Agneta; Bergqvist, David
Key Clinical Message: Neonatal aortic bifurcation thrombosis can cause occlusion of iliac arteries causing abnormal pelvic vasculature and claudication in childhood. A bifurcation graft normalizes the perfusion of the legs but not of the pelvis. In a girl, this does not preclude successful pregnancies in adult life. It has not been reported before. Abstract : Neonatal aortic bifurcation thrombosis can cause occlusion of iliac arteries causing abnormal pelvic vasculature and claudication in childhood. A bifurcation graft normalizes the perfusion of the legs but not of the pelvis. In a girl, this does not preclude successful pregnancies in adult life. It has not been reported before.